Digital humanities and digital social reading. (5th November 2021) - Rebora, Simone; Boot, Peter; Pianzola, Federico; Gasser, Brigitte; Herrmann, J Berenike; Kraxenberger, Maria; Kuijpers, Moniek M; Lauer, Gerhard; Lendvai, Piroska; Messerli, Thomas C; Sorrentino, Pasqualina
Abstract: Prominent among the social developments that the web 2.0 has facilitated is digital social reading (DSR): on many platforms there are functionalities for creating book reviews, 'inline' commenting on book texts, online story writing (often in the form of fanfiction), informal book discussions, book vlogs, and more. In this article, we argue that DSR offers unique possibilities for research into literature, reading, the impact of reading and literary communication. We also claim that in this context computational tools are especially relevant, making DSR a field particularly suitable for the application of Digital Humanities methods. We draw up an initial categorization of research aspects of DSR and briefly examine literature for each category. We distinguish between studies on DSR that use it as a lens to study wider processes of literary exchange as opposed to studies for which the DSR culture is a phenomenon interesting in its own right. Via seven examples of DSR research, we discuss the chosen approaches and their connection to research questions in literary studies.